A war criminal’s remorse: the case of Landžo and Plavšić - Simić, Olivera (Human rights review, 2020)
This paper analyses the role of remorse and apology in international criminal trials by juxtaposing two prominent cases of convicted war criminals Biljana Plavšić and Esad Landžo. Plavšić was the first and only Bosnian Serb political leader to plead guilty before the International Criminal Tribunal for the former Yugoslavia (ICTY). Her acknowledgement of guilt and purported remorse expressed during her ICTY proceedings was celebrated as a milestone for both the ICTY and the Balkans. However, she later retracted her remorse while serving her prison sentence. Landžo was a guard at the notorious Čelebići detention camp and did not acknowledge his guilt publicly during his ICTY trial. Seven years after his release from prison, Landžo personally confronted survivors and apologised to them. Through comparison of these two widely different cases, we illustrate varying roles criminal trials can play in offender’s reflection on his/her crimes (instrumental remorse versus catalytic role) and how relevance and resonance of war criminal’s remorse in and outside of the courtroom depend on how remorse is expressed and to whom (in abstracto during criminal proceedings versus personally face to face).